Cytotoxic Compounds from Alcyoniidae: An Overview of the Last 30 Years - Federico Cerri; Francesco Saliu; Davide Maggioni; Simone Montano; Davide Seveso; Silvia Lavorano; Luca Zoia; Fabio Gosetti; Marina Lasagni; Marco Orlandi; Orazio Taglialatela-Scafati; Paolo Galli (Marine Drugs, 2022)
The octocoral family Alcyoniidae represents a rich source of bioactive substances with intriguing and unique structural features. This review aims to provide an updated overview of the compounds isolated from Alcyoniidae and displaying potential cytotoxic activity. In order to allow a better comparison among the bioactive compounds, we focused on molecules evaluated in vitro by using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay, by far the most widely used method to analyze cell proliferation and viability. Specifically, we surveyed the last thirty years of research, finding 153 papers reporting on 344 compounds with proven cytotoxicity. The data were organized in tables to provide a ranking of the most active compounds, to be exploited for the selection of the most promising candidates for further screening and pre-clinical evaluation as anti-cancer agents. Specifically, we found that (22S,24S)-24-methyl-22,25-epoxyfurost-5-ene-3β,20β-diol (16), 3β,11-dihydroxy-24-methylene-9,11-secocholestan-5-en-9-one (23), (24S)-ergostane-3β,5α,6β,25 tetraol (146), sinulerectadione (227), sinulerectol C (229), and cladieunicellin I (277) exhibited stronger cytotoxicity than their respective positive control and that their mechanism of action has not yet been further investigated.